Antimicrobial & antimicrobial resistance - Scales, Danielle (2017)
By 2050, it is expected that antimicrobial resistance (AMR) will overtake cancer to become the world’s biggest killer. As the pharmaceutical industry spends less on antibiotic research and development, universities have an increasing role to play. As part of this degree, my two research projects approach AMR from different angles. The first takes a traditional approach to AMR, and uses transposon mutagenesis to identify novel novobiocin resistance mechanisms in Klebsiella pneumoniae. The second takes a genotypic approach and explores the application of anti-virulence drugs, which inhibit IscR in Yersinia pseudotuberculosis to disarm rather than kill the bacteria. Diversification is essential for the development of novel antimicrobial strategies.